Democracy and Dictatorship among the Catalan Intelligentsia: the Matteotti Affair and the Reflections of Francesc Cambó - Cattini, Giovanni C. (Journal of Catalan Intellectual History, 2012)
The debate over dictatorship and democracy is a fundamental feature of the cultural and political landscape that gave rise to the strategies and approaches of intellectuals between the two world wars. Their conceptions of the two systems weighed heavily in their reflections as liberal democratic ideals lost credibility and fell into decline. It is often said that the revolutions in Russia in 1917 and Italy in 1922 pushed intellectuals to choose between socialism and fascism. The political situation in Catalonia offers suggestive insights into this dilemma. More specifically, the present paper examines the debate sparked among Catalan intellectuals by the kidnapping and assassination of a socialist member of the Italian parliament, Giacomo Matteotti (1885-1924). The Matteotti affair coincided with the publication of a series of articles exploring the connections between democracy and dictatorship. Notable among these pieces are the contributions of the conservative Catalan nationalist leader Francesc Cambó (1876-1947), who wrote for the newspaper La Veu de Catalunya. Cambó’s articles, reprinted later in the same year in a book on Italian fascism, Entorn del feixisme italià, spawned a bitter refutation of his position that reached beyond the historical context. key words: Fascism, Democracy, Dictatorship, Nationalism, Intellectuals, Catalonia.